NEK2 promotes cancer cell progression and 5-fluorouracil resistance via the Wnt/β-catenin signaling pathway in colorectal cancer - Facai Cui; Yu Chen; Xiaoyu Wu; Weifeng Zhao (Discover Oncology)
Abstract Background Never-in-mitosis gene A-related-kinase-2 (NEK2) plays a pivotal role in malignant progression and chemotherapy sensitivity. This study aimed to elucidate the role of NEK2 in colorectal cancer (CRC) and its potential contribution to 5-fluorouracil (5‑FU) resistance mechanisms. Methods Quantitative real-time PCR (qRT‑PCR), western blotting, and immunohistochemical (IHC) staining were used to assess the expression of NEK2 in CRC tissues and cells. The effects of NEK2 and 5‑FU on the proliferation, apoptosis, migration, and invasion of cancer cells were investigated via Cell Counting Kit-8 (CCK-8), colony formation, flow cytometry, wound healing, and transwell assays, respectively. Methyl 3-(4-methylphenylsulfonamido) benzoate (MSAB) was used as a Wnt/beta (β)-catenin pathway inhibitor in this study. Results NEK2 expression was significantly upregulated in CRC tissues and cells compared to normal controls. High NEK2 expression in CRC tissues was correlated with advanced tumor-node-metastasis (TNM) stage, lymph node metastasis, distant metastasis, and a poor tumor prognosis. NEK2 overexpression promoted the proliferation, migration, and invasion of CRC cells. NEK2 overexpression inhibited the cytotoxic effect of 5-FU on CRC cells. NEK2 overexpression promoted the nuclear accumulation of β-catenin and activated the Wnt/β-catenin signaling pathway. MSAB reversed the stimulatory effect of NEK2 upregulation on proliferation and resistance to 5-FU in CRC cells. Conclusions In summary, NEK2 promotes cell survival and decreases sensitivity to 5-FU in CRC by activating the Wnt/β-catenin signaling pathway. Consequently, NEK2 holds promise as a potential therapeutic target for CRC management.